Handbook of research on new media literacy at the K-12 level issues and challenges - Tan, Leo Wee Hin, 1944-; Subramaniam, R. (Ramanathan), 1952- (Information Science Reference, 2009)
"This book provides coverage of significant issues and theories currently combining the studies of technology and literacy"--Provided by publisher.